2018
DOI: 10.1111/blar.12839
|View full text |Cite
|
Sign up to set email alerts
|

Alpine Masculinity: A Gendered Figuration of Capital in the Patagonian Andes

Abstract: This article investigates the Patagonian ecotourism industry and the spatial production of gender privilege. The analysis attends to how the spatial practices of park rangers, tourism guides and climbers create a gendered space of capital accumulation that devalues and marginalises othered subjects -such as women and non-alpine men -within specific domains of nature. Developing the concept of a figuration of capital, this article argues that the ecotourism industry has facilitated the rise of an alpine masculi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…Ademais, a aventura pode ocorrer em meios urbanos, embora, seja normalmente mais relacionada com cenários de natureza "selvagem", costumeiramente dominados pela figura masculina. Segundo Mendoza (2020), a indústria desses segmentos facilitou a ascensão de um sujeito masculino com base em valores corporais fundamentais: fisicalidade robusta, ética conservacionista e narração heroica sobre a natureza selvagem envolvente. Nesse mesmo sentido, pesquisas como a de Jordan & Gibson (2005), McArthur (1999) e Wilson e& Little (2005) revelam que geralmente, nesses segmentos, os homens obtêm o controle social da estrutura e até avaliam o que é considerado apropriado ou não para as turistas mulheres.…”
Section: Revisão De Literaturaunclassified
See 2 more Smart Citations
“…Ademais, a aventura pode ocorrer em meios urbanos, embora, seja normalmente mais relacionada com cenários de natureza "selvagem", costumeiramente dominados pela figura masculina. Segundo Mendoza (2020), a indústria desses segmentos facilitou a ascensão de um sujeito masculino com base em valores corporais fundamentais: fisicalidade robusta, ética conservacionista e narração heroica sobre a natureza selvagem envolvente. Nesse mesmo sentido, pesquisas como a de Jordan & Gibson (2005), McArthur (1999) e Wilson e& Little (2005) revelam que geralmente, nesses segmentos, os homens obtêm o controle social da estrutura e até avaliam o que é considerado apropriado ou não para as turistas mulheres.…”
Section: Revisão De Literaturaunclassified
“…Explorar o papel das mídias sociais na busca de companheiras com o mesmo objetivo, para conhecimentos sobre o destino e rotas para ajudar a superar uma série de restrições. (Mendoza, 2020) A indústria do ecoturismo facilitou a ascensão de um sujeito masculino com base em valores corporais fundamentais: fisicalidade robusta, ética conservacionista e narração heroica sobre a natureza selvagem envolvente. Inexistente.…”
Section: Inexistenteunclassified
See 1 more Smart Citation
“…Studies of masculinity in Argentina largely naturalize the link between masculinity and power. Many authors discuss the place of masculinity in high‐prestige social settings; for example, Badaró (2015) in the military, Mendoza (2020) with Patagonian park rangers, and Fuentes and Guinness (2019) with elite rugby clubs. Moving from socially privileged to subaltern men, while maintaining the link between masculinity and power, Whitson (2010) examines informal workers’ gender norms following the millennial economic crisis.…”
Section: Masculinities and The Nationmentioning
confidence: 99%
“…As hegemonic masculinity is not static and represents "the currently most honored way of being a man" (Connell and Messerschmidt 2005, 832), in the United States a hegemonically masculine man is generally understood as being white, economically privileged, cisgender, heterosexual, and able bodied. Scholars in outdoor education studies, ecotourism studies, and rural studies have identified variations of hegemonic masculinity in occupations such as outdoor education (Humberstone 2000), nature guiding (Mendoza 2020), and forestry (Brandth and Hauge 2005).…”
Section: Hegemonic Masculinity and Hybrid Masculinitymentioning
confidence: 99%